Some useful ideas for multistate protein design: Effect of amino acid substitutions on the multistate proteins stability and the rate of protein structure formation - Majorina, M. A.; Melnik, T. N.; Glukhov, A. S.; Melnik, B. S. (Frontiers in Molecular Biosciences, 2022)
The design of new protein variants is usually confined to slightly “fixing” an already existing protein, adapting it to certain conditions or to a new substrate. This is relatively easy to do if the fragment of the protein to be affected, such as the active site of the protein, is known. But what if you need to “fix” the stability of a protein or the rate of its native or intermediate state formation? Having studied a large number of protein mutant forms, we have established the effect of various amino acid substitutions on the energy landscape of the protein. As a result, we have revealed a number of patterns to help researchers identify amino acid residues that determine the folding rate and the stability of globular proteins states and design a mutant form of a protein with desired properties.